Physical Activity and Fruit and Vegetable Consumption among Organic Farmers - Lestari, Shaffira Deva; Pebrianti, Sandra; Nursiswati, Nursiswati (Media Karya Kesehatan, 2026)
Non-communicable diseases (NCDs) are closely related to lifestyle, particularly physical activity and the consumption of fruits and vegetables, which continue to be public health challenges. Organic farmers as a specific group have the potential for lower NCD risk due to the nature of their work and a lifestyle that tends to be more health-conscious. Organic farmers are known to have diverse physical activity patterns and close access to fruits and vegetables. This study aims to identify the physical activity habits and fruit and vegetable consumption of organic farmers. The research design used is quantitative descriptive. The population of this study consisted of organic farmers in Kecamatan Jatinangor and 30 respondents were selected using the snowball sampling approach. This study employed the International Physical Activity Questionnaire (IPAQ) and Food Frequency Questionnaire (FFQ) as research instruments. Data were analyzed using a quantitative descriptive approach, including frequency, proportion, and percentage calculations. The results showed that most organic farmers in Kecamatan Jatinangor were classified in high physical activity, totaling 27 respondents (90%), good fruit consumption with 26 respondents (86.7%), and good vegetable consumption with 28 respondents (93.3%). Therefore, it can be concluded that the majority of organic farmers in Kecamatan Jatinangor engage in high levels of physical activity as well as good fruit and vegetable consumption. Future studies are recommended to adopt qualitative approaches to explore factors influencing physical activity also fruit and vegetable consumption, as well as to collaborate with healthcare services, educational institutions, and farmer communities to support comprehensive health promotion programs. Keywords: Consumption, fruit, organic farmer, physical activity, vegetable.